Bimtek Penulisan Esai Naratif: Konten Budaya Lokal Sebagai Instrumen Preservasi Identitas Bangsa di Era Globalisasi - Ramadhani, Rakhmad Saiful; Ningsih, Masnia; Utama, Jenny Yudha; Dewi, Ratnaningrum Zusyana (Journal of Community Service and Society Empowerment, 2026)
Local cultural diversity is a fundamental asset and the soul of Indonesia's national identity, which is currently facing the threat of disintegration due to globalization and the dominance of global popular culture. This community service report evaluates the effectiveness of technical guidance on cultural essay writing as a strategy for revitalizing traditional heritage and strengthening community literacy. Through a Participatory Action Research (PAR) approach combined with the Asset-Based Community Development (ABCD) model, this activity facilitates the transformation of oral traditions into systematic narrative documentation. The program is implemented through a series of cultural asset identification, creative writing training, and publication assistance on digital platforms. The results show that essay writing not only improves technical literacy skills but also triggers critical awareness and a sense of pride in regional identity. The integration of local narratives with digital media has proven to be a cultural "bulwark" for the younger generation in responding to changes in socio-economic structures. The conclusion of this report emphasizes that cultural literacy through narrative essays is a long-term investment in maintaining national stability and identity sovereignty amidst the dynamics of global civilization.